I wonder why kangaroos have pouches and other questions about baby animals. - Wood, Jenny (New York : Southwestern, 2001)
Presents information and quirky facts about baby animals and their parents in a question and answer format.
Includes index.
Keywords: Animals -- Infancy -- Miscellanea; Parental behavior in animals -- Miscellanea; Questions and answers